Synthesis of Tamoxifen-Artemisinin and Estrogen-Artemisinin Hybrids Highly Potent Against Breast and Prostate Cancer - Fröhlich, Tony; Mai, Christina; Bogautdinov, Roman P.; Morozkina, Svetlana N.; Shavva, Alexander G.; Friedrich, Oliver; Gilbert, Daniel; Tsogoeva, Svetlana (ChemMedChem, 2020)
In the search for new and effective treatments of breast and prostate cancer, a series of hybrid compounds based on tamoxifen, estrogens, and artemisinin were successfully synthesized and analyzed for their in vitro activities against human prostate (PC-3) and breast cancer (MCF-7) cell lines. Most of the hybrid compounds exhibit a strong anticancer activity against both cancer cell lines – for example, EC50 (PC-3) down to 1.07 μM, and EC50 (MCF-7) down to 2.08 μM – thus showing higher activities than their parent compounds 4-hydroxytamoxifen (afimoxifene, 7; EC50=75.1 (PC-3) and 19.3 μM (MCF-7)), dihydroartemisinin (2; EC50=263.6 (PC-3) and 49.3 μM (MCF-7)), and artesunic acid (3; EC50=195.1 (PC-3) and 32.0 μM (MCF-7)). The most potent compounds were the estrogen-artemisinin hybrids 27 and 28 (EC50=1.18 and 1.07 μM, respectively) against prostate cancer, and hybrid 23 (EC50=2.08 μM) against breast cancer. These findings demonstrate the high potential of hybridization of artemisinin and estrogens to further improve their anticancer activities and to produce synergistic effects between linked pharmacophores.
CRIS-Team Scopus Importer:2020-07-10
Keywords: antitumor agents; artemisinin; breast cancer; estrogen; hybrids; prostate cancer; tamoxifen